KONSEP PENGGUNAAN RUANG DI KAWASAN ULEE LHEUE KOTA BANDA ACEH SEBAGAI RECREATIONAL WATERFRONT - Maulana Rahmat; Bakti Setiawan; Atrida Hadianti (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2023)
One of the areas that are planning and developing this public space is the Ulee Lheue Beach area. This can be seen from the infrastructure development that the government is trying to make use of the area. This study aims to see the conceptual success of the use of regional space. This research uses the descriptive quantitative deductive method. The scope location of the research object is the Ulee Lheue seaside area. The data obtained for research are questionnaires, interviews, and secondary data. The sample used in this research is a proportional random sampling method. The principle of coastal urban planning is the basis for urban or regional planning, which includes various considerations and planning components for the success of a good city or region. The principle regarding the concept of a recreational waterfront area by the beach of Ulee Lheue which is very successful relates to the interest of the people of Banda Aceh City towards the area by the beach of Ulee Lheue, namely the uniqueness of the area. And what works relates to natural resources, in the form of water quality in the area. While those that are not successful relate to inter-regional integrity within the area.